2018
DOI: 10.3389/fpsyg.2018.00928
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Children’s Connection to Nature Through Authentic Situations: The Case of Saving Salamanders at School

Abstract: The aim of this paper is to explore how children learn to form new relationships with nature. It draws on a longitudinal case study of children participating in a stewardship project involving the conservation of salamanders during the school day in Stockholm, Sweden. The qualitative method includes two waves of data collection: when a group of 10-year-old children participated in the project (2015) and 2 years after they participated (2017). We conducted 49 interviews with children as well as using participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 79 publications
(130 reference statements)
3
63
0
4
Order By: Relevance
“…These learning approaches focus less on outcomes, and more on what people want to learn and how they learn. Research from psychology (Krathwohl et al, 1964;Rowson, 2011), sociology (Everard et al, 2016), environmental education (Barthel et al, 2018;Chawla and Cushing, 2007;Ernst and Theimer, 2011) management studies and environmental management (Ballard and Belsky, 2010;, among other disciplines, emphasizes the role of experience, exploration, dialogue, and reflection in transformative learning processes. Below, we consider how each of these can contribute to more empowering responses to climate change.…”
Section: Transformative Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…These learning approaches focus less on outcomes, and more on what people want to learn and how they learn. Research from psychology (Krathwohl et al, 1964;Rowson, 2011), sociology (Everard et al, 2016), environmental education (Barthel et al, 2018;Chawla and Cushing, 2007;Ernst and Theimer, 2011) management studies and environmental management (Ballard and Belsky, 2010;, among other disciplines, emphasizes the role of experience, exploration, dialogue, and reflection in transformative learning processes. Below, we consider how each of these can contribute to more empowering responses to climate change.…”
Section: Transformative Learningmentioning
confidence: 99%
“…When discussing transformative learning in relation to climate change, research has suggested that learning needs to be exploratory and open-ended, making room for creative, unexplored practices (Barthel et al, 2018;Chawla, 2007;Giusti et al, 2018) that shine light on the inner dimensions of sustainability (O'Brien and Hochachka, 2010;O'Brien and Wolf, 2010;Scheffer et al, 2017;Sharma, 2017). In contrast to traditional learning approaches, which tend to stay within existing boundaries and ways of thinking, transformative learning involves questioning assumptions and challenging "the given" (Bateson, 1999;Sterling, n.d.).…”
Section: Explorationmentioning
confidence: 99%
“…Acting on such a vision could lead to the greening of cities and to a living environment for urban people that enables the broad-based development of pro-environmental values [13]. Drawing on the recent insights in ecological psychology, stewardship action may have a global sustainability implication in simultaneously shaping behavior and environmental attitudes among two-thirds of the global population in the urban Anthropocene [12,14,71]-a view with roots in Bem's [7] self-perception theory of attitude change, which assumes that people acquire positive attitudes toward an attitudinal object because of what they do behaviorally (as opposed to the opposite assumption that people behave in certain ways because they like it). For instance, food cultivation activities are a sustainability issue of great importance especially for people in cities [9,23,69].…”
Section: The Motivating Vision and Its Role For Wider Urban Sustainabmentioning
confidence: 99%
“…The literature in psychology and sociology suggests that such pro-environmental behavior in turn could shape inner motivations for broad-based environmental action, such as fostering a stronger connection to nature and enhanced levels of place-based well-being [7][8][9][10]. The massive scale and pace of global urbanization may lead to an alienation process in which a significant proportion of the future human population will find itself separated from sensory interaction with natural environments, which may lead to a broad-based social-ecological amnesia [11][12][13][14]. Civic ecology and stewardship are two concepts that illuminate civic restoration and the management of urban natural environments, and they are also argued to lead to learning, a deepening of connections with nature, and strengthened social bonds [5,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation